2018
DOI: 10.1002/2018gl077199
|View full text |Cite
|
Sign up to set email alerts
|

On Mars's Atmospheric Sputtering After MAVEN's First Martian Year of Measurements

Abstract: Mars likely lost a significant part of its atmosphere to space during its history. The sputtering of the atmosphere, by precipitating planetary heavy pickup ions accelerated by the solar wind, is one of the processes that could have significantly contributed to this atmospheric escape, in particular since the cessation of its global magnetic field, 4.0–4.1 Gyr ago. We present a 2 year baseline analysis of Mars Atmosphere and Volatile EvolutioN (MAVEN) observations of the precipitating flux. We use this measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 27 publications
3
30
1
1
Order By: Relevance
“…In order to reconstruct the precipitating flux, we used the method developed by Leblanc et al () and Leblanc et al (, ). We focused on a range in altitude between 200 and 350 km, close enough to the Martian exobase so that any ion within this range of altitude with velocity at least than 75° with direction respect to the local nadir direction has a very large probability to impact Mars' atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…In order to reconstruct the precipitating flux, we used the method developed by Leblanc et al () and Leblanc et al (, ). We focused on a range in altitude between 200 and 350 km, close enough to the Martian exobase so that any ion within this range of altitude with velocity at least than 75° with direction respect to the local nadir direction has a very large probability to impact Mars' atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…HELIOSARES has been successfully used to characterize the oxygen component of the exosphere that was measured by MAVEN at different seasons and at various SZAs (Leblanc et al, ). More recently, the model was used to calculate the expected increase of the exospheric density induced by pickup ion sputtering assuming the typical precipitating flux that was measured by MAVEN (Leblanc et al, ). The study showed that deep in the nightside, the nonthermal component of Ar is dominated by particles ejected by pickup ion sputtering.…”
Section: Comparison Between Ngims Ar Measurements and Heliosares Simumentioning
confidence: 99%
“…In the HELIOSARES model, three main sources of exospheric Ar can be identified: the Ar atoms ejected into the exosphere by collision with nonthermal O that were produced by the dissociative recombination of O 2 + (Figure b); the thermal component, which corresponds to the thermal expansion of atmospheric Ar (Figure c); and the sputtered component, which corresponds to Ar atoms that are ejected by pickup ions sputtering the atmosphere (Figure d). One should note that in the case of this simulation, we simulated O + precipitating particles assuming the average dayside and nightside differential energy distribution of the precipitating particles that was observed by MAVEN/SWIA from 2015 to 2017 (Leblanc et al, ). …”
Section: Comparison Between Ngims Ar Measurements and Heliosares Simumentioning
confidence: 99%
See 2 more Smart Citations